The Managing Emergencies in Paediatric Anaesthesia global rating scale is a reliable tool for simulation‐based assessment in pediatric anesthesia crisis management. Issue 12 (26th June 2013) - Everett, Tobias C.; Ng, Elaine; Power, Daniel; Marsh, Christopher; Tolchard, Stephen; Shadrina, Anna; Bould, Matthew D.
Summary: Introduction: The use of simulation‐based assessments for high‐stakes physician examinations remains controversial. The Managing Emergencies in Paediatric Anaesthesia course uses simulation to teach evidence‐based management of anesthesia crises to trainee anesthetists in the United Kingdom (UK) and Canada. In this study, we investigated the feasibility and reliability of custom‐designed scenario‐specific performance checklists and a global rating scale (GRS) assessing readiness for independent practice. Methods: After research ethics board approval, subjects were videoed managing simulated pediatric anesthesia crises in a single Canadian teaching hospital. Each subject was randomized to two of six different scenarios. All 60 scenarios were subsequently rated by four blinded raters (two in the UK, two in Canada) using the checklists and GRS. The actual and predicted reliability of the tools was calculated for different numbers of raters using the intraclass correlation coefficient (ICC) and the Spearman–Brown prophecy formula. Results: Average measures ICCs ranged from 'substantial' to 'near perfect' ( P ≤ 0.001). The reliability of the checklists and the GRS was similar. Single measures ICCs showed more variability than average measures ICC. At least two raters would be required to achieve acceptable reliability. Conclusions: We have established the reliability of a GRS to assess the management of simulated crisis scenarios in pediatric anesthesia, and this tool is feasible within the setting of a research study. The global rating scale allows raters to make a judgement regarding a participant's readiness for independent practice. These tools may be used in the future research examining simulation‐based assessment.